Os parques proletários e os subúrbios do Rio de Janeiro: Aspectos da política governamental para as favelas entre as décadas de 1930 e 1960 - Rute Imanishi Rodrigues (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The present paper explores the links between governmental policies towards Rio de Janeiro's favelas, between the 1930's and 1960's, focusing on actions related to the land, and the beginning or enlargement of determined nucleus of favelas in the city suburbs. The paper presents the results of a research in primary sources, such as: Victor Tavares Moura collection (mentor of Parques Proletários Provisórios program),newspapers of the time, and documents published in Diário oficial da Uni\~ao (DOU). According to that research, even though many favelas nucleuses have begun spontaneously, some governmental actions led to their consolidation and expansion. In the Leopoldina Zone there is evidence that such actions were important to the beginning of large slums like Penha, Manguinhos, Vigário Geral, Maré e Morro do Alem\~ao.
Keywords: R68; 330; favelos; slums; Rio de Janeiro